2020
DOI: 10.1016/j.isci.2020.101464
|View full text |Cite
|
Sign up to set email alerts
|

Deglycosylated Azithromycin Targets Transgelin to Enhance Intestinal Smooth Muscle Function

Abstract: Summary Azithromycin (AZM) has been widely used as an antibacterial drug for many years. It has also been used to treat delayed gastric emptying. However, it exerts several side effects. We found that deglycosylated AZM (Deg-AZM or CP0119), an AZM metabolite, is a positively strong intestinal agonist that may result in the intestinal mobility experienced by patients after AZM administration. We confirmed that Deg-AZM can function strongly on intestinal peristalsis and identified transgelin as its po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous studies found that PLK1-targeted siRNA could effectively inhibit the proliferation of various malignant tumors, block tumor cells at the G2/M stage, and induce tumor cell apoptosis and sensitivity to radiotherapy and chemotherapy (40)(41)(42). Therefore, the development of PLK1 inhibitors as therapeutic targets may provide novel ideas regarding an individualized treatment for basal-cell type breast cancer (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that PLK1-targeted siRNA could effectively inhibit the proliferation of various malignant tumors, block tumor cells at the G2/M stage, and induce tumor cell apoptosis and sensitivity to radiotherapy and chemotherapy (40)(41)(42). Therefore, the development of PLK1 inhibitors as therapeutic targets may provide novel ideas regarding an individualized treatment for basal-cell type breast cancer (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…The mice were treated with atropine (15 mg kg −1 ) (CAS 51-55-8, NARUREWILL, China) and sucralfate (5 mg kg −1 ) (CAS 54182-58-0, DEMO Medical Technology, China) twice daily by gavage for 2 days. 33 Then, the mice were treated with 200 μL antibiotic cocktail (ampicillin 1 g L −1 , metronidazole 1 g L −1 , vancomycin 0.5 g L −1 , and neomycin 0.5 g L −1 ) (Sigma, USA) once a day for 3 days. Afterwards, the mice were randomized into 3 groups: the model group, FMT-MRS group and FMT-LGGs group.…”
Section: Methodsmentioning
confidence: 99%
“…We proposed a strategy to enhance the stability of ZEB1 by inhibiting the interaction between TAGLN and USP1 and reducing the retention of USP1 in the cytoplasm. According to previous studies, some macrocyclic monomers have excellent binding activity to TAGLN [ 18 ]. Therefore, we randomly selected 200 plant-derived extracts with macrocyclic monomer and screened for inhibitors of the TAGLN/USP1 interactive interface by virtual docking.…”
Section: Resultsmentioning
confidence: 99%